A case of multiple familial trichoepitheliomas responding to treatment with the Hedgehog signaling pathway inhibitor vismodegib - Baur, Vera; Papadopoulos, Thomas; Kazakov, Dmitry V; Agaimy, Abbas; Hartmann, Arndt; Isbary, Georg; Wirtz, Ralph M; Schultz, Erwin S (Virchows Archiv, 2018)
Multiple familial trichoepitheliomas (MFT) is an autosomal dominantly inherited disease characterized by multiple skin appendage tumors. We describe a patient showing a continuous spectrum of follicular differentiated neoplasms including classical trichoepitheliomas but also infiltrative growing and finally metastasizing malignant follicular differentiated tumors. Germline mutation analysis revealed a nonsense mutation in the cylindromatosis (CYLD) gene. Gene expression analysis by real-time PCR of tumor tissue showed overexpression of glioma-associated oncogene Gli1 mRNA. Treatment with the Hedgehog pathway inhibitor vismodegib resulted in a significant regression of the highly differentiated trichoepitheliomas. Gli upregulation is indicative of an active Hedgehog signaling pathway. We hypothesize that its upregulation is indirectly caused by CYLD mutation which promotes tumor development. Vismodegib treatment could thus provide a new treatment option for patients with this debilitating disorder.
Keywords: počítačová rentgenová tomografie; anilidy; Anilides; CYLD; fenotyp; Zinc Finger Protein GLI1; protein Gli1; nesmyslný kodon; Male; Tomography, X-Ray Computed; nádory kůže; Humans; lidé středního věku; upregulace; Treatment Outcome; deubikvitinizační enzym CYLD; genetická predispozice k nemoci; mužské pohlaví; rodokmen; dědičnost; Hedgehog pathway; lidé; Vismodegib; Signal Transduction; Pyridines; Brooke syndrome; Codon, Nonsense; imunohistochemie; Deubiquitinating Enzyme CYLD; Up-Regulation; signální transdukce; výsledek terapie; Trichoepithelioma; pyridiny; protinádorové látky; Genetic Predisposition to Disease; Pedigree; Antineoplastic Agents; Heredity; Neoplastic Syndromes, Hereditary; Immunohistochemistry; Middle Aged; Skin Neoplasms; dědičné nádorové syndromy; Phenotype